TeleBCI: remote user training, monitoring, and communication with an evoked-potential brain-computer interface. Issue 3 (1st October 2020) - Geronimo, Andrew; Simmons, Zachary
ABSTRACT: Brain-computer interfaces (BCIs) can serve as a type of augmentative and alternative communication (AAC) for individuals with amyotrophic lateral sclerosis (ALS). One hindrance to BCI adoption is the complexity of providing training and support for users. This paper describes the teleBCI interface used to train end-users in the operation of a virtual keyboard using an evoked potential BCI. Fifteen patients with motor neuron disease and their communication partners were included in the study. Teams completed 8 sessions of P300 BCI training virtually with the researcher. Over time, teams required less help to complete physical, computer, and BCI-specific tasks associated with device use. A subset of users experienced improved performance over sessions, progressing to utilize the full functionality of the speller and communicate with a nurse partner over a telemedicine interface. Integration of telemedicine in ALS care provides new opportunities for how BCI-AAC are deployed and used.